Perencanaan Aplikasi Bioengineering Tanah pada Kawasan Bekas Longsor di Desa Cililin, Kecamatan Cililin, Kabupaten Bandung Barat, Provinsi Jawa Barat - Dyah Nursita Utami; Akhmadi Puguh Raharjo (Agency for the Assessment and Application of Technology / Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
Landslides are the third most frequent disaster in Indonesia. One of these landslides occurred on March 10, 2017 in residential area of Jatiradio, Cililin Village, Cililin Sub-District, West Bandung Regency, West Java Province. Post-incident investigations have produced information regarding the characteristics of the area and recommendations for disaster mitigation. At present it is known that there are still problems left unsolved in the area that need to be mitigated. The purpose of this study is to identify those unsolved problems at the study site and formulate solutions to the problem using a soil bioengineering approach. Among all the data that need to be collected are the condition of both existing vegetation and subsurface profile on the former landslide slopes at the study site. Data from the observations were then analyzed to produce recommendations regarding the application of soil bioengineering at the study site. From this study, pine trees (Pinus merkusii) is recommended to be planted on the slopes and areas around the rock gabions. This type of vegetation has fulfilled four pre-determined criterias related to the function of slope protection and groundwater regulation for this particular area and is considered suitable to be applied to the study site.